Identification of five novel SCN1A variants - Zeng, Baitao; Zhang, Haoyi; Lu, Qing; Fu, Qingzi; Yan, Yang; Lu, Wan; Ma, Pengpeng; Feng, Chuanxin; Qin, Jiawei; Luo, Laipeng; Yang, Bicheng; Zou, Yongyi; et al. (Frontiers in Behavioral Neuroscience, 2023)
Background: Epilepsy is characterized by recurrent unprovoked seizures.Mutations in the voltage-gated sodium channel alpha subunit 1 (SCN1A) gene are the main monogenic cause of epilepsy. Type and location of variants make a huge difference in the severity of SCN1A disorder, ranging from the mild phenotype (genetic epilepsy with febrile seizures plus, GEFS+) to the severe phenotype (developmental and epileptic encephalopathies, DEEs). Dravet Syndrome (DS) is an infantile-onset DEE, characterized by drug-resistant epilepsy and temperature sensitivity or febrile seizures. Genetic test results reveal SCN1A variants are positive in 80% DS patients and DS is mainly caused by de novo variants.Method: Trio-whole exome sequencing (WES) was used to detect variants which were associated with clinical phenotype of five probands with epilepsy or twitching. Then, Sanger sequencing was performed to validate the five novel SCN1A variants and segregation analysis. After analyzing the location of five SCN1A variants, the pathogenic potential was assessed.In this study, we identified five novel SCN1A variants (c.4224G>C, c.3744_3752del, c.209del, c.5727_5734delTTTAAAACinsCTTAAAAAG and c.5776delT) as the causative variants. In the five novel SCN1A variants, four were de novo and the remaining one was inherited. All novel variants would be classified as "pathogenic" or "likely pathogenic".The five novel SCN1A variants will enrich the SCN1A mutations database and provide the corresponding reference data for the further genetic counseling.